2003
DOI: 10.1073/pnas.2135499100
|View full text |Cite
|
Sign up to set email alerts
|

Elevated gene expression levels distinguish human from non-human primate brains

Abstract: Little is known about how the human brain differs from that of our closest relatives. To investigate the genetic basis of human specializations in brain organization and cognition, we compared gene expression profiles for the cerebral cortex of humans, chimpanzees, and rhesus macaques by using several independent techniques. We identified 169 genes that exhibited expression differences between human and chimpanzee cortex, and 91 were ascribed to the human lineage by using macaques as an outgroup. Surprisingly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
419
4
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 459 publications
(458 citation statements)
references
References 42 publications
22
419
4
3
Order By: Relevance
“…An alternate, albeit related, explanation would be that regions with low genetic variance have greater functional constraints on their determinants of cortical thickness, such that genetic mutations influencing these regions will typically be eliminated quickly from the population through purifying selection. Comparative genomic experiments have shown that a subset of neurally-expressed genes have evolved more rapidly in humans than in other primates [Chimpanzee Sequencing and Analysis Consortium, 2005;Dorus et al, 2004;Khaitovich et al, 2005]; both gene expression changes and protein sequence modification have accelerated in humans relative to nonhuman primates [Caceres et al, 2003;Enard et al, 2002;Gu and Gu, 2003;Hsieh et al, 2003;Uddin et al, 2004]. The findings of increased genetic variance in evolutionarily recent structures may represent a remnant of these rapid neurogenetic changes that accompanied our divergence from other primates.…”
Section: Discussionmentioning
confidence: 99%
“…An alternate, albeit related, explanation would be that regions with low genetic variance have greater functional constraints on their determinants of cortical thickness, such that genetic mutations influencing these regions will typically be eliminated quickly from the population through purifying selection. Comparative genomic experiments have shown that a subset of neurally-expressed genes have evolved more rapidly in humans than in other primates [Chimpanzee Sequencing and Analysis Consortium, 2005;Dorus et al, 2004;Khaitovich et al, 2005]; both gene expression changes and protein sequence modification have accelerated in humans relative to nonhuman primates [Caceres et al, 2003;Enard et al, 2002;Gu and Gu, 2003;Hsieh et al, 2003;Uddin et al, 2004]. The findings of increased genetic variance in evolutionarily recent structures may represent a remnant of these rapid neurogenetic changes that accompanied our divergence from other primates.…”
Section: Discussionmentioning
confidence: 99%
“…The aim has been to characterize general trends in the evolution of gene expression rather than to identify specific genes of interest. To date, conclusions about the selection pressures acting on gene expression have been conflicting 2,3,6,[11][12][13] .These studies have all relied on data collected from arrays using gene probes that were designed on the basis of human sequences only. However, sequence mismatches affect hybridization intensity and can therefore bias estimates of gene expression differences between species 14 .…”
mentioning
confidence: 99%
“…The aim has been to characterize general trends in the evolution of gene expression rather than to identify specific genes of interest. To date, conclusions about the selection pressures acting on gene expression have been conflicting 2,3,6,[11][12][13] .…”
mentioning
confidence: 99%
“…Large-scale gene expression studies showed that an overall upregulation of genes involved in synaptic transmission and metabolic processes that support it has occurred on the human lineage (e.g., ref. 14), suggesting that higher neuronal activity may have coevolved with greater brain size and other changes.…”
mentioning
confidence: 99%